Toward a Theory of Competitive Price Adjustment - Eden, Benjamin (Review of Economic Studies, 1981)
Journal Article Toward a Theory of Competitive Price Adjustment Get access Benjamin Eden Benjamin Eden University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 199–216, https://doi.org/10.2307/2296880 Published: 01 April 1981 Article history Received: 01 March 1980 Accepted: 01 September 1980 Published: 01 April 1981